INCREASING REGENERATION EFFICIENCY BY RECYCLING ALKANOLAMINES - Rakhimov , Ganisher (Sanoatda raqamli texnologiyalar, 2024)
This article aims to improve the efficiency of the gas purification process by determining the composition of the used alkanolamine solutions and regenerating them using the absorption method of gas purification from sour components.